2019
DOI: 10.1186/s12870-019-1706-1
|View full text |Cite
|
Sign up to set email alerts
|

Grafting alleviates potassium stress and improves growth in tobacco

Abstract: Background Potassium is a nutrient element necessary for tobacco growth. Tobacco leaves with high potassium content are elastic and tough, rich in oil. And the same time, potassium can also improve the scent and aromatic value of flue-cured tobacco by regulating the synthesis of aromatic hydrocarbons in leaves.. It is an important quality indicator for flue-cured tobacco. However, the potassium concentration in tobacco leaves in most areas of China is generally lower than the global standard for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…NKT1 is an inwardly rectifying K + channel gene that mediates K + uptake in Shakerlike family expressed in tobacco cells [30]. In our previous studies, it was found that low potassium levels can induce down-regulation expression of this gene [19]. This corresponds to the results of this experiment.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…NKT1 is an inwardly rectifying K + channel gene that mediates K + uptake in Shakerlike family expressed in tobacco cells [30]. In our previous studies, it was found that low potassium levels can induce down-regulation expression of this gene [19]. This corresponds to the results of this experiment.…”
Section: Discussionsupporting
confidence: 84%
“…Regardless of whether there was normal K supply or K starvation, the K content of the plants with the W genotype tobacco rootstock was significantly higher than the plants with the Y genotype. Combined with our previous research [19], grafting not only improved tobacco growth, but also increased the whole-plant K content of the Y genotype tobacco compared with the nongrafted original variety. Another interesting observation in the experiment was that the distribution of K + in the tobacco plant changed under K starvation.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…According to our previous studies, grafting affects the absorption and utilization of K 1 in tobacco, especially that of a series of strategies for coping with low potassium stress, and also changes the circulation and redistribution pattern of K 1 in tobacco plants (Hu et al, 2019). This will have a significant impact on the photosynthesis of the tobacco leaves and will directly change the synthesis and transportation of assimilation products.…”
mentioning
confidence: 99%